Diverse climbing strategies in aroid vines: functional adaptations and environmental drivers - Yu, Pinger; Weng, Shufei; Zhang, Bo; Huang, Yichun; Xu, Feican (Frontiers in Plant Science, 2025)
Aroid vines are an essential group for vertical space resource utilization in tropical rainforests and serve as key materials for vertical greening in urban landscapes and home gardening. Understanding their climbing strategies is crucial for rainforest ecological conservation and alleviating urban green space shortages. However, current research on the climbing growth of aroid vines remains fragmented. This article systematically reviews the existing literature, synthesizing advances in three key research domains: functional climbing-type classification and global distribution of climbing aroids, climbing strategies, and influencing factors. The review explores the climbing strategies and morphological plasticity from the perspectives of roots, stems, and leaves. Additionally, factors such as light conditions, host surfaces characteristics, mechanical contact, and growth direction are analyzed to understand the growth traits and environmental adaptability of aroid vines. The review highlights that: (1) Aroid vines can be classified by life form into terrestrial vines, epiphytic vines, and semi-epiphytic vines, and by the degree of leaf differentiation into isomorphic, allomorphic, and heteromorphic vines. However, their current life-form classification systems remain to be refined; (2) Root adhesion serves as the core climbing strategy, characterized by the dimorphism of aerial roots, which facilitate attachment through clasping roots; (3) Aroid vines exhibit pronounced morphological plasticity to cope with environmental transitions from the terrestrial to the canopy, reallocating resources toward aboveground organs—enhancing water and nutrient transport through the proliferation of feeder roots, stem thickening, and hydraulic optimization, while promoting photosynthetic efficiency and drought tolerance via heterophyllous leaf development; (4) Negative phototropism drives the search for supports, light intensity regulates leaf morphological development, and host surface roughness and material significantly affect attachment efficiency and biomass allocation. Mechanical contact and gravity direction influence growth through hormone homeostasis, coordinating resource distribution. Based on current findings, future research directions and actionable recommendations are proposed to provide a theoretical foundation for the further exploitation and utilization of aroid vines.